Duck Rearing - Akbar, M A; Sreehari, S.; Yadav, J S (Indian Farming, 2015)
Ducks are suitable for integrated farming systems such as duck-cumfish farming and duck farming with rice cultivation. In duck-cum-fishfarming the droppings of ducks serve as feed for the fishes. Under integrated duck farming with rice cultivation, the ducks perform four essential functions, intertillage as they search for food with their spoon like bills. Ducks are good exterminators of potato beetles, grasshoppers, snails and slugs. Ducks can be used to freethe water bodies from mosquitoe pupae and larvae.